KINETIC MODELING ON AMIDE HYDROLYSIS, DRUG RELEASE AND MUCOSAL PERMEATION OF INDOMETHACIN IN THE COMPOSITION OF SELECTED SEMISOLID VEHICLES - Nadezhda A. Ivanova; Tsvetelina S. Stefanova; Ivelin R. Iliev; Georgi S. Stoyanov; Kameliya Zh. Bratoeva (Peytchinski Publishing, 2018)
The present study aims to reveal the role of a semi-solid vehicle in the composition of Indomethacin dosage forms for their physical and chemical stability, in vitro and ex vivo behavior. Three types of hydrogels and emulgels were prepared with gelling agents Methylcellulose 2%, Poloxamer 407 20% and Carbomer 940 1%. Each preparation was observed for physical and chemical stability at 5°C and 25°C within 3 months. Test formulations, along with USP standard Indomethacin gel and combined marked product Indextol,were subjected to in vitro drug release test and ex vivo permeation study, using porcine intestinal mucosa on Franz diffusion cell. A hypothesis was built to predict steady-state plasma concentration (Css) of Indomethacin for each formulation following mucosal administration. Results revealed sustained chemical stability of all emulgels for the period observed and significantly lower chemical stability of the corresponding hydrogels. Methylcellulose hydrogel (at both temperatures) and emulgel (at 25°C) showed signs of phase separation, while all other formulations kept their physical appearance for the duration of the study. Methylcellulose emulgel along with Poloxamer 407 hydrogel showed highest cumulative drug release in 12 hours (58.01% and 55.00%, respectively). Same formulations exhibited also highest drug permeation rate (Jss) through mucosa (10.55 µg.cm-2.h-1 and 13.20 µg.cm-2.h-1, respectively) and highest predicted value of plasma concentration (Css up to 100.49 µg.l-1 and 125.71 µg.l-1, respectively), whereas highest drug deposition in mucosal tissue was detected for Poloxamer 407 emulgel (2.1 mg.cm-3).